Utility model and usability evaluation instrument for elderly’s pain management mobile applications / Umm-E-Mariya Shah - Umm-E-Mariya , Shah (2021)
The elderly population is growing rapidly worldwide. It has turned out to be highly important in many industries to take into account the specific needs of older people. Old age people are more at risk of having chronic illness and pain is amongst their common ailments. Pain is prevalent to involve high societal cost and the most disabling condition among the other major chronic diseases. This highlights the importance of proper pain self-management to improve quality of life via mHealth technology. Nevertheless, the elderly have certain limitations in the use of mobile technology because of physical, perception, cognitive or motivational constraints. Analysis of existing electronic pain diaries and pain management applications reveals that the applications are not comprehensive in terms of self-management, and were developed without the clinical advice and elderly’s involvement. This research aims at identifying the utility and usability aspects of the pain management mobile applications that provide ease of use and acceptance among the elderly. The utility aspect was first studied. Essential features of pain self-management were identified from systematic literature review. Based on the findings of the review and the identified features in the previous studies, a conceptual utility model to aid understanding of the concept of pain management was proposed. The conceptual utility model was further evaluated and verified by nine medical doctors for its accuracy and comprehensiveness. Moreover, a focus group discussion was conducted with the medical doctors to identify their data accessibility needs, mechanism to get their involvement, acceptability of the systems in their daily workflow and other concerns about the pain management applications used by the elderly. This was followed by a questionnaire-based utility survey among the elderly patients to understand their utility preferences of the pain management applications. The finalised utility model can be used to guide development of and verify suitability and comprehensiveness of pain self-management mobile applications. On the usability aspect, an extensive review of literature was conducted to find out the domain-specific usability problems. This results in a taxonomy of design concerns, usability issues, and their solutions/recommendations. The elderly’s barriers in technology use and research gap in the elderly specific usability evaluation was also identified. Based on the findings, a usability evaluation instrument that maps the usability measures with the elderly’s barriers was proposed. The content of the instrument was verified by five experts (usability, linguistics and medical). A usability study, followed by usability evaluation and face validity, was performed with sixteen elderly participants on the pre-selected pain management mobile applications. The usability study and evaluation helped to test the reliability of the proposed usability evaluation instrument and identify the real-world issues in the applications use. The instrument also provides graphical visualization of the mapping of usability measures with the elderly’s barriers and scores of various artefacts. The graphical details will be helpful in identifying the areas of usability improvement and the scores could be helpful in comparing usability of different applications. Keywords: